BOD and DO Identification of Jeneberrang-River Water as Water Source. (May 2018) - Basir, Basir; Haris, Ibrahim Abdul
Abstract: Water is a part of life on the surface of the earth. It is not a new substance which no life on earth can survive without water. This study aims to identify the quality of river water of jeneberang as municipal waterworks (PDAM) raw regarding to turbidity parameters, BOD, and DO. The used methodology is observational with descriptive approach. The sampling technique was done by grasping each sample for turbidity parameter, BOD and DO in four IPAM water inlet of Makassar City. This sampling was conducted at Laboratory of Environmental Health Engineering Center (BTKL) and Disease Control using Nephelometric Turbidity Unit, Titrimetry, and Spectrophotometric method. The results of the examination showed that the turbidity level> 5 NTU, so it is not eligible to be drunk directly. The levels for BOD and eligibles for not exceeding the specified limits are <3 mg / l and <25 mg / l and in DO for Maccini Sombala <4 mg / l region, so it is not eligible. The conclusion in this research that turbidity parameter, BOD and DO qualify as the raw water of PDAM have to be processed so that water can be drunk by society.